A Novel Scoring System Based on Preoperative Routine Blood Test in Predicting Prognosis of Atypical Meningioma - Chen, Xiaoyong; Wang, Guojun; Zhang, Jianhe; Zhang, Gaoqi; Lin, Yuanxiang; Lin, Zhangya; Gu, Jianjun; Kang, Dezhi; Ding, Chenyu (Frontiers in Oncology, 2020)
Purpose The aim of this study was to explore the correlation and clinical significance of preoperative fibrinogen and neutrophil-lymphocyte ratio F-NLR scoring system with 3-year progression-free survival PFS of patients with atypical meningioma. Material and method: Clinical, pathological, radiological, and laboratory variables were collected to analyze their correlation with 3-year PFS in the training set with 163 patients. Patients were classified by different F-NLR scores 0, 1, or 2. External validation for the predictive value of F-NLR scoring system was performed in the validation set with 105 patients. Results: Overall, 37.3% (100 of 268) of the enrolled patients were male. The scoring system showed good performance in predicting 3-year PFS AUC=0.872, 95CI=0.811-0.919, sensitivity=66.1, specificity=93.3, and Youden index=0.594. DeLong’s test indicated that the AUC of F-NLR scoring system was significantly greater than that of fibrinogen level and NLR (Z=2.929, P=0.003; Z=3.376, P0.001). Multivariate Cox analysis revealed that tumor size (HR=1.39, 95CI=1.10-1.76, P=0.007), tumor location (HR=3.11, 95CI=1.60-6.95, P=0.001), and F-NLR score (score of 1: HR=12.78, 95CI=3.78-43.08, P 0.001; score of 2: HR=44.58, 95CI=13.02-152.65, P 0.001) remained significantly associated with 3-year PFS. The good predictive performance of F-NLR scoring system was also demonstrated in the validation set (AUC=0.824, 95CI=0.738-0.891, sensitivity = 62.5, specificity = 87.9, and Youden index = 0.504). Conclusion: Our study confirmed the correlation and clinical significance of preoperative F-NLR scoring system with 3-year PFS of patients with atypical meningioma. A prospective and large-scale study is required to validate our findings.